2013
DOI: 10.1155/2013/212803
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Behavior of Natural Fe2O3 from Lhoong Iron Ore Mining Area, Aceh Province, Indonesia

Abstract: The mineral composition and magnetic behavior of nano-Fe 2 O 3 of iron ore from Lhoong mining area, Aceh province, were studied. The iron ore was prepared by mechanical milling method. The mineral and chemical compositions of samples were investigated by XRD and XRF analysis tests. The XRF test showed that the Lhoong iron ore contains Fe 2 O 3 (93.88%) in association with other isomorphous impurities, such as SiO 2 , MnO, and Al 2 O 3 , in varying proportions. Compared to XRD results, it was consistent with XR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Some studies reported that the interactions of the biological systems with nanoparticles were influenced by the corona phenomena-derived protein layer, with subsequent changes of their surfaces and increasing their sizes (Simon-Deckers et al, 2008). In respect of nanoparticle sizes, some authors speculated the size and the changes of the physical shape of nanoparticles could be a mechanistic factor for their toxicity (Di Pasqua et al, 2008; Rahwanto et al, 2013). At the same time, other researchers have argued that the toxicity of nanoparticles is not entirely dependent on their surface charge and size, and other surface properties such as functional groups or other pollutants are more important ((Malvindi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that the interactions of the biological systems with nanoparticles were influenced by the corona phenomena-derived protein layer, with subsequent changes of their surfaces and increasing their sizes (Simon-Deckers et al, 2008). In respect of nanoparticle sizes, some authors speculated the size and the changes of the physical shape of nanoparticles could be a mechanistic factor for their toxicity (Di Pasqua et al, 2008; Rahwanto et al, 2013). At the same time, other researchers have argued that the toxicity of nanoparticles is not entirely dependent on their surface charge and size, and other surface properties such as functional groups or other pollutants are more important ((Malvindi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing this abundant resource streamlines production and purification, yielding pristine nanoparticles for exploration in biomedical applications. 13 Inspired by recent studies, such as those by Jalil et al (2019), 14 revealing enhanced magnetic behavior in nano iron oxide from Lhoong iron ore by Rahwanto et al (2013), 15 presenting silica-free micro/nano Fe 2 O 3 particles with high iron content by Almeida et al, 16 demonstrating PEG-MN nanoparticles with remarkable properties by Kareem et al (2015). 17 Our work was motivated to contribute to this evolving landscape.…”
Section: Introductionmentioning
confidence: 95%
“…Considering its geometrical structure, hematite (α-Fe 2 O 3 ) is one of iron oxides among magnetite (Fe 3 O 4 ) and maghemit (-Fe 2 O 3 ). Hematite compound (α-Fe 2 O 3 ) become most popular of among the iron oxide compounds due to their polymorphic properties, biochemical uniqueness, magnetic, catalytic and other properties [6][7][9][10][11][12]. Hematite has a rhombohedral shape with a central hexagonal structure and a dense oxygen lattice.…”
Section: Introductionmentioning
confidence: 99%